2019
DOI: 10.3847/2041-8213/ab5f67
|View full text |Cite
|
Sign up to set email alerts
|

The Acceleration and Confinement of Energetic Electrons by a Termination Shock in a Magnetic Trap: An Explanation for Nonthermal Loop-top Sources during Solar Flares

Abstract: Nonthermal loop-top sources in solar flares are the most prominent observational signature that suggests energy release and particle acceleration in the solar corona. Although several scenarios for particle acceleration have been proposed, the origin of the loop-top sources remains unclear. Here we present a model that combines a large-scale magnetohydrodynamic simulation of a two-ribbon flare with a particle acceleration and transport model for investigating electron acceleration by a fast-mode termination sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 62 publications
10
68
0
Order By: Relevance
“…Particle acceleration in the flare's impulsive phase proceeds in the environment where the newly reconnected magnetic field lines emanating from the CME-trailing current sheet interact with the underlying flare arcades. Particles can be accelerated there in collapsing magnetic traps (Somov & Kosugi 1997) or by Fermi-type acceleration in the "termination" shocks formed by reconnection outflows of the CMEtrailing current sheet (Masuda et al 1994;Chen et al 2015;Kong et al 2019). The flare environment is rich in turbulence, waves, and a fractal electric field, which have also been suggested as possible particle acceleration mechanisms (see the review by Zharkova et al 2011, and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…Particle acceleration in the flare's impulsive phase proceeds in the environment where the newly reconnected magnetic field lines emanating from the CME-trailing current sheet interact with the underlying flare arcades. Particles can be accelerated there in collapsing magnetic traps (Somov & Kosugi 1997) or by Fermi-type acceleration in the "termination" shocks formed by reconnection outflows of the CMEtrailing current sheet (Masuda et al 1994;Chen et al 2015;Kong et al 2019). The flare environment is rich in turbulence, waves, and a fractal electric field, which have also been suggested as possible particle acceleration mechanisms (see the review by Zharkova et al 2011, and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…We model the acceleration and transport of electrons by coupling the Parker transport equation (Parker 1965) with a macroscopic MHD simulation of the solar flare. This general framework has 5 been discussed previously (Kong et al 2019(Kong et al , 2020Li et al 2018) and here we only provide a salient description.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the dramatic difference between the kinetic scales (∼1-10 cm for electrons and ∼1-10 m for protons) and the macroscopic flare scale (∼ 10 8 m), numerical modeling of particle acceleration in solar flares has been very challenging. Recently, we have developed a macroscopic kinetic model for energetic particles that combines a particle acceleration and transport model with the MHD simulation of solar flares (Kong et al 2019(Kong et al , 2020. Kong et al (2019) showed that electrons can be efficiently accelerated by the TS and a magnetic trap plays a critical role in both confining and accelerating electrons in the looptop region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations of interplanetary shocks provide a unique opportunity to systematically understand the system where shocks interact with large-scale turbulence and accelerate energetic particles. Understanding how these processes work is also important to many other space, solar and astrophysical systems (Giacalone, 2017a;Kong et al, 2019b).…”
Section: Discussion and Summarymentioning
confidence: 99%